Environmental pollution size of the Bishkek Solid Waste Landfill and treatment of generated leachate wastewater - Mehmet Kobya; Kubat Kemelov; Venera Edilbek Kyzy; Nurzat Shaykieva; Mustafa Dolaz (MANAS: Journal of Engineering)
The disposal of municipal solid wastes (MSW) is one of the important issues today. The MSW is generally disposed of in a landfill. The disintegration of wastes in landfill generates the wastewater known as leachate and it became one of the budding environmental impacts. The landfill leachate seeps into natural ponds next to the Bishkek (Kyrgyzstan) landfill. The MSWs are dumped with an irregular landfill in Bishkek, and it has been observed that this situation creates many environmental pollution problems (air pollution due to the combustion of wastes and generated biogas, due to leakage of leachate from the landfill) around the landfill. The leachate in the ponds is not treated and leaks into the environment. In this study, the potential of the coagulation-flocculation(CF) and electrooxidation (EO) processes was investigated for the treatment of leachate from the sanitary landfill located in Bishkek-Kyrgyzstan. The initial COD (1400 ± 50 mg/L), TOC (540 ± 15 mg/L), and ammonia nitrogen (315 ± 10 mg/L) from landfill leachate were treated by the CF process as 33, 23, and 14% at pH 6.5 with alum dosage of 5 g/L, and 40, 29 and 10.1% at pH 8.5 with ferric chloride dosage of 5 g/L, respectively.Removal efficiencies at applied currents of 1.0, 3.0, and 5.0 A with an EO reactor using boron-doped diamond (BDD) plate anode and stainless steel (SS) plate cathode were 67.20, 88.30, and 97.90% for COD, 60.10, 85.38, and 95.53% for TOC, and 48.9, 94.6 and 99.8% for ammonia nitrogen, respectively. As a result, it was seen that Bishkek’s irregular solid waste landfilling leachate, which causes environmental pollution, was effectively treated with the EO process. By establishing a regular landfill, Bishkek municipal solid wastes must be disposed of in the landfill and treated of the leachate.